Jia-Wei-Yu-Ping-Feng-San Attenuates Group 2 Innate Lymphoid Cell-Mediated Airway Inflammation in Allergic Asthma - Xue, Lingna; Li, Cui; Ge, Guangbo; Zhang, Shaoyan; Tian, Liming; Wang, Yu; Zhang, Huiyong; Ma, Zifeng; Lu, Zhenhui (Frontiers in Pharmacology, 2021)
The incidence of asthma has increased in recent decades. Although corticosteroids and bronchodilators are used in clinical practice, the control of asthma remains a challenge. Allergic asthma is characterized airway inflammation mediated by type 2 immune response. Group 2 innate lymphoid cells (ILC2s) are an important source of type 2 cytokines IL-5 and IL-13, which contribute to the progress of asthma. Jia-Wei-Yu-Ping-Feng-San (JWYPFS), a traditional Chinese medicine, has been widely used to treat asthma in China. In this study we investigated the mechanisms of JWYPFS in the treatment of asthma, especially the effect on ILC2s important in airway inflammation. Female C57BL/6 mice were sensitized and challenged with OVA to establish a model of allergic asthma. Airway hyperresponsiveness was examined by direct airway resistance analysis. Inflammatory cell counts were determined in bronchoalveolar lavage fluid (BALF). Inflammatory cell infiltration and mucus hypersecretion in lung tissue sections was observed by HE and PAS staining, respectively. The numbers and proportions of ILC2s as well as the ILC2s-related transcription factors GATA3, IRF4, and type 2 cytokines were measured in lung tissue samples. Additionally, ILC2s were collected from mouse lung; ILC2s-related cytokines and GATA3 and IRF4 were evaluated after IL-33-induced activation of ILC2s in vitro. Elevated inflammatory cells, mucus secretion, airway hyperresponsiveness and type 2 cytokines in the OVA-treated asthma group indicated that an allergic asthma model had been established. JWYPFS treatment attenuated airway resistance and reduced inflammatory cells including eosinophils, and inhibited mucus production and type 2 cytokines in these asthmatic mice. Moreover, JWYPFS treatment dramatically decreased the numbers and proportions of ILC2s and the mRNA levels of GATA3 and IRF4. In an in vitro experiment JWYPFS significantly suppressed GATA3, IRF4 and type 2 cytokine expression, including IL-5 and IL-13 in IL-33-stimulated ILC2s. JWYPFS alleviates ILC2s-mediated airway inflammation, suggesting that JWYPFS might be an effective agent to treat allergic asthma.